2016
DOI: 10.4172/2167-0420.1000294
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Pelvic Alignment among Never-Pregnant Women,Pregnant Women, and Postpartum Women (Pelvic Alignment and Pregnancy)

Abstract: Objective: To compare the pelvic alignment among never-pregnant women, pregnant women, and postpartum women. Methods: A total of 177 nulliparous women (mean age, 18.9 ± 1.0 years), 45 pregnant women between the third and tenth month of pregnancy (mean age, 29.4 ± 3.8 years), and 124 primiparous women between the first and sixth months after delivery (mean age, 30.1 ± 4.4 years) were enrolled in this study. Pelvic alignment was measured by using the anterior superior iliac spine (ASIS) and posterior superior il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 19 publications
(31 reference statements)
0
13
0
1
Order By: Relevance
“…Major gender differences were shown in the joint angles during phases of sit to stand movement [18]. Also, pelvic alignment was different among never-pregnant, pregnant, and postpartum women [19].…”
Section: Discussionmentioning
confidence: 94%
“…Major gender differences were shown in the joint angles during phases of sit to stand movement [18]. Also, pelvic alignment was different among never-pregnant, pregnant, and postpartum women [19].…”
Section: Discussionmentioning
confidence: 94%
“…1,974 studies were identified, but only 18 met all inclusion criteria (Table 1). Five studies reported changes in pelvic alignment during pregnancy and postpartum recovery [17][18][19][20][21]. Five studies focused on pelvic alignment after childbirth [22][23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, measurements differed between studies, precluding use of a meta-analysis. Three studies included 100 -200 participants; however, authors and their institutions were the same in two studies [17,19,21]. One of the three studies was a cross-sectional study and compared participants [19]; thus, it did not observe how pelvic alignment changed during and after pregnancy [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Имеются исследования, демонстрирующие асимметрию таза, развивающуюся при беременности вследствие более значительного расширения таза во фронтальной плоскости, чем в сагиттальной. Именно эта асимметрия является причиной болей в пояснице у беременных [11].…”
Section: Introductionunclassified